Lighting effects on beef carcass grade factors - Donald H. Kropf; Melvin C. Hunt; H.R. Cross; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 1983)
Beef carcass quality factors were evaluated under 25 different lighting systems (five lighting types each at five light intensities). Cool White fluorescent caused the darkest and most mature lean score, but marbling quantity score was not affected by lighting type or intensity. Lean was scored progressively brighter and more youth with increasing lighting intensity.
Keywords: Cattlemen' s Day; 1983; Report of progress (Kansas State University. Agricultural Experiment Station); 427; Beef; Carcass; Light intensities; Quality grade